Studi Analisis tentang Serapan Bahasa Arab dan Arabisasi di Indonesia - Alfina Nur Fadhilah; Achmad Hafi; Muflihah (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2024)
Abstract This article discusses the process of Arabic loanwords into Indonesian, categorizing the borrowed words based on the changes in pronunciation and meaning. There are four main categories: (1) Pronunciation and meaning remain the same, (2) Pronunciation changes while meaning remains the same, (3) Pronunciation remains the same while meaning changes, and (4) Both pronunciation and meaning change. This process reflects the dynamic linguistic interaction between the two cultures. The article also explains the history of ta'rib in Indonesia, which began in the 7th century with the spread of Islam, as well as the role of education in introducing Arabic terms. Furthermore, it outlines the forms and examples of ta'rib in daily language, religious terminology, law, and the positive and negative impacts of Arabization. Positive impacts include vocabulary enrichment and ease in understanding scientific terms, while negative impacts include reduced linguistic diversity and the loss of local cultural identity. Thus, ta'rib is a complex phenomenon influencing the development of language and culture in Indonesia.